A pattern of roses - Peyton, K. M. (New York Crowell, 1973)
The discovery of old drawings with the same initials as his leads a sixteen-year-old boy on a journey into the past where he relives the experiences of the artist.
Keywords: Time travel -- Fiction; England -- Fiction